Integrated Analytical, Numerical, and Observational Approaches for Evaluating Soft Soil Consolidation Behavior at Patimban, Subang - Teguh Afiffurokhim; Mohamad Khoiri; Mahendra Andiek Maulana (Interdisciplinary Social Studies, 2025)
The construction of high embankments on soft soil in the Patimban area, Subang, is associated with risks of long-term settlement and lateral deformation due to the soil’s high compressibility and low permeability. Inaccurate prediction of consolidation behavior may adversely affect construction schedules and post-construction infrastructure performance. This study aims to evaluate the consolidation behavior of soft soil through the integration of three approaches: analytical analysis based on Terzaghi’s consolidation theory, numerical modeling using PLAXIS 2D, and validation using field instrumentation data, including settlement plates, piezometers, and inclinometers. The results indicate that the predicted ultimate settlement of an 8.8 m high embankment is relatively consistent between the analytical method (yielding 1.110 m) and the numerical method (yielding 1.165 m). Under existing conditions with an embankment height of 2.762 m at 416 days, the measured settlement of 40 mm shows good agreement with the analytical prediction of 54 mm. Numerical modeling also successfully represents lateral deformation behavior, with a predicted lateral displacement of 28.56 mm, which is consistent with the inclinometer measurement of 26.10 mm. The consolidation time analysis reveals that, in the absence of ground improvement measures, the time required to reach 90% degree of consolidation (U??) is estimated to be approximately 42.8 years. This study confirms that integrating analytical, numerical, and field observational approaches enhances the accuracy of soft soil consolidation evaluation and provides a robust basis for technical decision-making regarding the necessity of consolidation acceleration in large-scale infrastructure projects